Amylin Analog Pramlintide Induces Migraine‐like Attacks in Patients. Issue 6 (8th April 2021) - Ghanizada, Hashmat; Al‐Karagholi, Mohammad Al‐Mahdi; Walker, Christopher S.; Arngrim, Nanna; Rees, Tayla; Petersen, Jakeb; Siow, Andrew; Mørch‐Rasmussen, Mette; Tan, Sheryl; O'Carroll, Simon J.; Harris, Paul; Skovgaard, Lene Theil; et al.
Abstract : Objective: Migraine is a prevalent and disabling neurological disease. Its genesis is poorly understood, and there remains unmet clinical need. We aimed to identify mechanisms and thus novel therapeutic targets for migraine using human models of migraine and translational models in animals, with emphasis on amylin, a close relative of calcitonin gene‐related peptide (CGRP). Methods: Thirty‐six migraine without aura patients were enrolled in a randomized, double‐blind, 2‐way, crossover, positive‐controlled clinical trial study to receive infusion of an amylin analogue pramlintide or human αCGRP on 2 different experimental days. Furthermore, translational studies in cells and mouse models, and rat, mouse and human tissue samples were conducted. Results: Thirty patients (88%) developed headache after pramlintide infusion, compared to 33 (97%) after CGRP ( p  = 0.375). Fourteen patients (41%) developed migraine‐like attacks after pramlintide infusion, compared to 19 patients (56%) after CGRP ( p  = 0.180). The pramlintide‐induced migraine‐like attacks had similar clinical characteristics to those induced by CGRP. There were differences between treatments in vascular parameters. Human receptor pharmacology studies showed that an amylin receptor likely mediates these pramlintide‐provoked effects, rather than the canonical CGRP receptor. Supporting this, preclinical experiments investigating symptoms associated with migraine showed that amylin treatment, like CGRP, caused cutaneous hypersensitivity and light aversion in mice. Interpretation: Our findings propose amylin receptor agonism as a novel contributor to migraine pathogenesis. Greater therapeutic gains could therefore be made for migraine patients through dual amylin and CGRP receptor antagonism, rather than selectively targeting the canonical CGRP receptor. ANN NEUROL 2021;89:1157–1171